Implementing Effective Strategies to Foster Environmental Care Character among Students - Nurul Khasana; Dholina Inang Pambudi; Nazori Masaei (The Indonesian Institute of Science and Technology Research, 2023)
This study employs a qualitative research approach with a case study design to investigate the teacher's strategy in developing students' environmental caring character, as well as the factors that support and hinder this strategy in the 3T area. The research subjects consist of school principals, teachers, and students at public elementary school Belitang, Indonesia. Data were collected using interviews, observations, and documentation analysis, and analyzed through data reduction, presentation, and conclusion. The study finds that the teacher's strategy in cultivating the character of caring for the environment for students is successful, as it involves planning, directing, and implementing environmentally sound policies, providing motivation, creating conducive learning conditions, giving positive directions, and changing student behavior towards the environment. Supporting infrastructure, such as the availability of landfills and cleaning equipment in each class, also contributes to this success. However, the lack of a garbage pit remains an inhibiting factor, leading to the scattering of final waste in the school's backyard.